Isolation and identification of bacteria-producing cellulose from tropical fruit for Halal capsule application - Awang, Nursyahidatul Azwa; Amid, Azura; Jimat, Dzun Noraini (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2018)
Bacterial cellulose (BC) is pure cellulose synthesized by various species of bacteria. Raising demands on bacterial cellulose is due to its simpler and pure structure. It has plenty of applications in various industries such as food, medical and cosmetics, thus, allowing it to be the choice in halal industries application as a substitute for non-halal gelatine. However, challenges arise during the BC production such as high production cost and low volumetric yield. In this study, BC is studied to overcome the barriers in BC production. This present study carried out the isolation and identification of cellulose producing bacteria from selected tropical fruits. The bacteria were isolated from eight different tropical fruit sources using HestrinSchramm media in static culture condition. Morphological and molecular identification by microscopic observation, gram staining, and 16S rRNA analysis were conducted to identify the characteristics and strain of the new isolate. Next, the selected colonies were challenged to grow in agitating condition using modified HS media. The effects of carbon concentration and agitation speed on the production of cellulose were investigated using on central composite design (CCD). Characterization of BC was carried out by scanning electron microscopy (SEM) and Fourier Transform Infrared spectroscopy (FTIR) analysis. The result indicated that three new cellulose-producing bacteria were successfully isolated and similar to Enterobacter sp. SJZ-5, Bacterium sp NLAE-zl-H356, and Bulkhoderia sp. RD_DACAR_02 through morphological and molecular analysis. The most potent strain; which is similar to Enterobacter sp. SJZ-5 was named as Enterobacter sp.M003 has been chosen for BC optimization study for high BC production using modified HS media. Optimization of bacterial cellulose production using response surface methodology (RSM) with 13 runs indicated that the optimal production parameters are 17.57 g/L for carbon concentration in 277 rpm for agitation speed. It is expected that the newly isolated bacteria will be able to provide an alternative to gelatine for halal capsule production, thus minimizing non-halal gelatine usage.